Higher education, internet usage, and Chinese female’s identification with patriarchal perspective: An empirical analysis considering moderating effect - Jiacheng Gao; Yue Liu (Цифровая социология, 2023)
Based on data from a sample of 377 females in the 2018 Chinese General Social Survey, this study constructs a logit model considering moderating effect to estimate the effect of receiving higher education on the patriarchal perspective held by Chinese females, and examines the moderating effect of internet usage on the relationship between receiving higher education and the patriarchal perspective. As a result of the study, the authors came to the following conclusions. Firstly, receiving higher education will have a direct and significant improvement effect on the patriarchal perspective held by Chinese females, reducing their identification with the patriarchal perspective, especially for Chinese rural females. Secondly, internet usage will not directly have a significant effect on the patriarchal perspective held by Chinese females, but it will indirectly have a significant moderating effect on the patriarchal perspective held by Chinese rural females by receiving higher education. The more frequently Chinese rural females use the Internet, the weaker the effect of receiving higher education on their patriarchal perspective. Ultimately, when Chinese rural females use the Internet very frequently, receiving higher education will make them identify with the patriarchal perspective. Thirdly, the act of marriage will significantly strengthen the identification with the patriarchal perspective for both Chinese urban and rural females. However, engaging in household investment activities will significantly reduce the patriarchal perspective of Chinese urban females, while Chinese rural females will only gradually identify more with the patriarchal perspective as they grow older.